A cavitation model considering thermodynamic and viscosity effects. Issue 6 (1st October 2018) - Pang, Kaiwen; Li, Yaojun; Yang, Wei; Liu, Zhuqing
Abstract : Purpose: This study aims to develop and validate a new cavitation model that considers thermodynamic effects for high-temperature water flows. Design/methodology/approach: The Rayleigh–Plesset equation and "B-factor" method proposed by Franc are used to construct a new cavitation model called "thermodynamic Zwarte–Gerbere–Belamri" (TZGB) by introducing the thermodynamic effects into the original ZGB model. Furthermore, the viscous term of the Rayleigh–Plesset equation is considered in the TZGB model, and the model coefficients are formulated as a function of temperature. Cavitating flows around the NACA0015 hydrofoil under different water temperatures (25°C, 50°C and 70°C) at the angle of attack of 5° are calculated. Findings: Results of the investigated temperatures show good agreement with the available experimental data. Given that the thermodynamic and viscosity effects are included in the TZGB model and the model coefficients are treated as a function of temperature, the TZGB model shows better performance in predicting the pressure coefficient distribution and length of cavity than the original ZGB cavitation model and other models do. The TZGB model aims to determine the thermodynamic and viscosity effects and perform better than the other models in predicting the mass transfer rate, particularly in high-temperature water. Originality/value: The TZGB model shows potential in predicting the cavitating flows at high temperature and the computational cost of this model is similar to that of the original ZGB model.